An Empirical Study on the Sustainable Tourism in West Sumatera: A Case of Bilih Fish Product - Pepy Afrilian (Jurnal Pembangunan Nagari, 2022)
This aim of this research is focused on the innovation of the culinary products called Bilih Fish (Mystacoleucus Padangensis) as the tourism destination and as one of the main products on the sustainable tourism ecosystem in West Sumatera of Indonesia. Bilih fish (Mystacoleucus Padangensis) is endemic and only can be found in Singkarak Lake of West Sumatera Province. The research problem was about sustainability issue of the Bilih fish on the supply chain ecosystem as well as significant strength of sustainable tourism in West Sumatera, Indonesia. The research used qualitative approach using primary data sources where data were collected by using direct non-participant observation and structured-interview techniques. Interview was conducted with Bilih fish entrepreneur. In addition, this research also used the secondary data used research notes from the Singkarak Geographical Indication Society (MIGS) which was tabulated on the data analysis by using validity and triangulation techniques. This research shows strategic ecosystem of fisherman Bilih fish integrated into tourists empowering local society for a sustainable tourism.